1997
DOI: 10.1021/ac960557q
|View full text |Cite
|
Sign up to set email alerts
|

On-Line HPLC Electrospray Mass Spectrometry of Phosphorothioate Oligonucleotide Metabolites

Abstract: Metabolism of 2'-deoxyphosphorothioate oligonucleotides ISIS 11061 and ISIS 11637 was examined with capillary gel electrophoresis (CGE) and on-line HPLC electrospray mass spectrometry (HPLC/ES-MS). Oligonucleotides were isolated from plasma, liver, and kidneys of rats injected with ISIS 11061 and ISIS 11637. Metabolites found in plasma were consistent with 3'-exonuclease activity. Metabolites isolated from liver and kidney were consistent with 3'- and/or 5'-exonuclease activity. HPLC/ES-MS analysis of ISIS 110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 14 publications
3
63
0
Order By: Relevance
“…These data are consistent with the nuclease resistance of 2Ј-MOE-modified nucleotides placed in the 3Ј-and 5Ј-terminal portions of ISIS 301012 (Zhang et al, 1995). There was a notable absence of metabolites ranging from 16 to 19 nucleotides, suggesting little to no exonuclease products that are often seen with unmodified phosphorothioate oligodeoxynucleotides (Temsamani et al, 1994;Cummins et al, 1996;Gaus et al, 1997). The similarity of the excretion metabolite pattern across species suggests similar enzymes are responsible for metabolic cleavage of oligonucleotides.…”
Section: Discussionsupporting
confidence: 61%
“…These data are consistent with the nuclease resistance of 2Ј-MOE-modified nucleotides placed in the 3Ј-and 5Ј-terminal portions of ISIS 301012 (Zhang et al, 1995). There was a notable absence of metabolites ranging from 16 to 19 nucleotides, suggesting little to no exonuclease products that are often seen with unmodified phosphorothioate oligodeoxynucleotides (Temsamani et al, 1994;Cummins et al, 1996;Gaus et al, 1997). The similarity of the excretion metabolite pattern across species suggests similar enzymes are responsible for metabolic cleavage of oligonucleotides.…”
Section: Discussionsupporting
confidence: 61%
“…Herein, we showed that our assay is highly sensitive and specific toward the parent compound and its metabolites, as it detects only the 3V-end intact sequence of G3139 at a single nucleotide resolution, with little or no cross-reactivity with the putative 3V-end metabolites (33,34). In contrast, the assay was not selective toward 5V metabolites; however, 5V-end metabolism has not been considered a major pathway (34 -36).…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with the nuclease resistance of 2Ј-MOE-modified nucleotides placed in the 3Ј-and 5Ј-terminal portions of ISIS 104838 . There was a notable absence of metabolites ranging from 16 to 19 nucleotides in length, suggesting little to no exonuclease products, which are often seen with unmodified phosphorothioate oligodeoxynucleotides (Temsamani et al, 1994;Gaus et al, 1997;.…”
Section: Discussionmentioning
confidence: 99%